2017
DOI: 10.1111/tpj.13445
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Arabidopsis thaliana SNF1‐related‐kinase 1 (SnRK1)‐activating kinase 1 (SnAK1) and SnAK2 on SnRK1 phosphorylation status: characterization of a SnAK double mutant

Abstract: Arabidopsis thaliana SNF1-related-kinase 1 (SnRK1)-activating kinase 1 (AtSnAK1) and AtSnAK2 have been shown to phosphorylate in vitro and activate the energy signalling integrator, SnRK1. To clarify this signalling cascade in planta, a genetic- and molecular-based approach was developed. Homozygous single AtSnAK1 and AtSnAK2 T-DNA insertional mutants did not display an apparent phenotype. Crossing of the single mutants did not allow the isolation of double-mutant plants, whereas self-pollinating the S1-/- S2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…Also, to circumvent the restrictions imposed by fixed number of genomic sequences, an array of well‐designed cotranslational and posttranslational layers of regulations and modifications are thus implemented (Guerra et al, ; Natan, Wells, Teichmann, & Marsh, ; Schütze, Harter, & Chaban, ; Withers & Dong, ; Zoschke, Chotewutmontri, & Barkan, ). Phosphorylation, the most abundant posttranslational modifications (PTMs), intimately involved in almost every signalling cascades act as precise molecular triggers (Chen et al, ; Coursol et al, ; Glab et al, ). It also creates exponential increase in the number of mature functional forms of a protein, generated from fixed subset of translational products (Prabakaran et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, to circumvent the restrictions imposed by fixed number of genomic sequences, an array of well‐designed cotranslational and posttranslational layers of regulations and modifications are thus implemented (Guerra et al, ; Natan, Wells, Teichmann, & Marsh, ; Schütze, Harter, & Chaban, ; Withers & Dong, ; Zoschke, Chotewutmontri, & Barkan, ). Phosphorylation, the most abundant posttranslational modifications (PTMs), intimately involved in almost every signalling cascades act as precise molecular triggers (Chen et al, ; Coursol et al, ; Glab et al, ). It also creates exponential increase in the number of mature functional forms of a protein, generated from fixed subset of translational products (Prabakaran et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On 3% sorbitol plates, in which the osmolarity was identical to that of the glucose‐ and sucrose‐supplemented plates, we observed no difference in growth between the wild‐type and the double mutant (Figure S1c). These results indicate that GRIK1 and GRIK2 specifically function in high‐glucose conditions, which is consistent with the reported phenotype of the grik1‐1 grik2‐1 mutant (Glab et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Recently, Glab et al . () have shown that the grik1‐1 grik2‐1 mutant could be rescued by sugar supplementation, yet the mature plant was stunted and sterile. The grik1‐2 grik2‐1 double mutant used here grew and reproduced normally under our growth‐room conditions (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations